OPTIMALISASI KUALITAS PELAYANAN MAHASISWA MELALUI PENGELOLAAN ARSIP DINAMIS DI PERPUSTAKAAN POLITEKNIK NEGERI MANADO - Jufrina Mandulangi; Juliet P.T. Makinggung; Sonny Kasenda; Frans Luntungan (Journal of Business Administration (JBA), 2022)
Libraries are institutions that carry out service-based activities. The fact is that to borrow books in the library needs long time affecting completion of students’ final project. There are also library officers serving students angrily. Consequently, many students look for books elsewhere. It is assumed that the optimization of student service quality is influenced by dynamic archive management at the Manado State Polytechnic Library. This study uses quantitative analysis in the form of multiple regression and correlation levels by carrying out several tests, namely classical tests such as multicollinearity, heteroscedasticity, and autocorrelation tests using the SPSS version 26 computer program. The results of the research showed that archive management storage systems, archive management officers, archive managemet knowledge have a positive and significant impact on students’ satisfaction. Meanwhile, archive managemet equipment had no effect on students’ satisfaction.